Characteristics stability of cheese whey-tomato juice fermented beverages with pectin and CMC addition. (October 2019) - Saidah, N; Nurhartadi, E; Nursiwi, A; Sari, A M; Utami, R
Abstract: The aim of this study was to investigate the chemical and microbiological stability of 12 days of storage (±4°C) of fermented beverages from cheese whey and tomato juice with addition of pectin:carboxy methyl cellulose combination (0%:0%; 0.15%:0.25%; 0.25%:0.15%; 0.2%:0.2%; 0.1%:0.3%) and to determine the best formula to find out it's hypocholesterolemic effects. Fermented cheese whey beverages was prepared from cheese whey:tomato juice (95%:5%), sucrose (10% w/v), and 5 variation of pectin:CMC combination. This research used a Completely Random Design (CRD) with one factor, combination of pectin and CMC. The result was analyzed by applying one-way analysis of variance (ANOVA) followed by Duncan test with 5% significant level. The result showed that during 12 days of storage, the addition of pectin:CMC combination in fermented beverages from cheese whey reduced the rate of pH, antioxidant activity, total lactic acid bacteria, and the rate of lactic acid rise. The best formula of fermented beverage from cheese whey and tomato juice is fermented beverage with 0.1%:0.3% (w/v) of pectin:CMC addition which has 34.636% of hypocholesterolemic effect.